Steadying the ship: Can export proceeds repatriation policy stabilize Indonesian exchange rates amid short-term capital flow fluctuations? - Sondang Marsinta Uli Panggabean; Mahjus Ekananda; Beta Yulianita Gitaharie; Leslie Djuranovik (Economies, 2025)
This paper investigates the impact of repatriated export proceeds on exchange rate volatility in Indonesia. By applying a time-varying parameter vector autoregression (TVP-VAR) model with stochastic volatility, we assess whether the impact of repatriated export proceeds can dampen the effect of short-term capital flows. Our findings indicate that the influence of export proceeds on exchange rate volatility varies over time, with no evidence supporting its ability to dampen the impact of short-term capital flows in the short and intermediate terms. Furthermore, we identify a reversal pattern in the impacts of both repatriated export proceeds and short-term foreign capital flows after 3-5 days, suggesting a potential need to evaluate policies aimed at dampening short-term capital flow impacts on exchange rate volatility. Our results are robust across a range of sensitivity and robustness checks, confirming the reliability of our findings.
Keywords: E58; F31; G15; 330; export proceeds repatriation; exchange rate volatility; short-term capital flows